Effectiveness of laparoscopic adenomyomectomy on perinatal outcomes - Yosuke Ono; Hajime Ota; Yoshiyuki Fukushi; Hikaru Tagaya; Yasuhiko Okuda; Osamu Yoshino; Hideto Yamada; Shuji Hirata; Shinichiro Wada (Gynecology and Minimally Invasive Therapy, 2023)
Objectives: The objective of this study was to observe the influence of laparoscopic adenomyomectomy on perinatal outcomes. Materials and Methods: The retrospective cohort study included 43 pregnant cases with adenomyosis who did not undergo laparoscopic surgery before pregnancy (nonsurgery group; 26 cases) and did (surgery group; 17 cases). To evaluate the impact of surgery on perinatal outcomes, nine obstetric complications including preterm delivery, hypertensive disorder of pregnancy, placental malposition, oligohydramnios, gestational diabetes mellitus, uterine rupture, abruptio placentae, and postpartum hemorrhage were selected. One obstetric complication was counted as one point (Maximum 9 points for one person). The obstetrical morbidity was compared by adding up the number of relevant events (0–9) between the two groups. Apgar score, umbilical artery pH (UApH), neonatal intensive care unit (NICU) admission, and neonatal death were also examined. Results: The surgery group had a significantly lower prevalence of fetal growth restriction compared to the nonsurgery group (nonsurgery vs. surgery; 26.9%, 7/26 vs. 0%, 0/17: P = 0.031). No differences were found in the morbidity of the nine obstetric complications (19.2%, 45/234 vs. 13.7%, 21/153), gestational weeks (mean ± standard deviation, 37.2 ± 2.4 vs. 36.4 ± 3.2), birth weight (2573.6 ± 557.9 vs. 2555.4 ± 680.8 g), Apgar score (1, 5 min; 8.0 ± 0.7 vs. 7.7 ± 1.2, 8.9 ± 0.6 vs. 8.5 ± 1.8), UApH (7.28 ± 0.08 vs. 7.28 ± 0.06), NICU admission (26.9%, 7/26 vs. 41.2%, 7/17), and neonatal death (0%, 0%) between both groups. Conclusion: Laparoscopic adenomyomectomy may not increase obstetric complications, although attention must be paid to uterine rupture during pregnancy.